AKТИВІЗАЦІЯ УЯВИ СТУДЕНТІВ У ПРОЦЕСІ ВИКЛАДАННЯ ДИРИГЕНТСЬКО-ХОРОВИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2006)
The authors are considering the essence of imagination and a significance in the work of choirmaster. The contest and results of experimental work on activation of imagination of future teachers of music in process of teaching of conductor's chorol subjects have beck analyzed. The main principles of corresponding method and the ways of their realization have been defined as well.